China's renminbi internationalization - Chan, Elgin (2023)
China has achieved some success in its Renminbi (RMB) internationalization strategy over the last two decades. Recent international sanctions imposed on Russia for its invasion of Ukraine have fueled China’s determination to expedite this strategy in order to protect Chinese national security and economic interests. While the United States has taken steps to counter China’s RMB internationalization initiatives and to maintain the existing role of the US dollar (USD), a more intensive US-China competition in this arena is anticipated because RMB internationalization is closely linked to China’s strategic priorities.